TRANSPORT OF U- AND TH-SERIES NUCLIDES IN A BALTIC SHIELD WATERSHED AND THE BALTIC SEA - Porcelli D.; Andersson P.S.; Baskaran M.; Wasserburg G.J. (My University, 2001)
The transport of Th, Ra, and 210Pb from a continental source region and through an estuarine environment was investigated. Unlike previous studies, here both short- and long-lived nuclide data were obtained for river inputs, river water, and estuarine waters. The mire-rich Kalix River drainage basin was chosen as a typical northern shield area because this river may represent typical waters flowing into the Arctic and northern seas.Groundwaters from bedrock and glacial tills have comparable Th isotope concentrations and do not exhibit significant Th isotopic shifts relative to host rocks. The extensive peat deposits of the basin receive groundwater discharges and concentrate Th and U (but not Ba and Ra), which cause high 230Th/232Th ratios in mire waters. However, mire outflows do not have a significant impact on Th and Ra isotopic compositions of the river.Overall weathering characteristics for the basin are obtained from the river data. The 230Th/232Th, 228Ra/226Ra, and 226Ra/Ba river ratios are comparable to those of source rocks, consistent with similar release rates of these nuclides from U-, Th-, and Ba-bearing minerals. River ratios of (230Th/238U)AR and (226Ra/238U)AR are <1, so that Th and possibly Ra are accumulating in the weathering regions, and the weathering profile is still evolving. Low (228Ra/232Th)AR and (226Ra/230Th)AR ratios indicate that Th is preferentially retained over Ra. River (234Th/238U)AR ratios are greater than (230Th/238U)AR ratios and suggest that in systems where river inputs are well characterized, these ratios can be used to calculate Th transit times through the watershed. Filtration data indicate that although a dominant fraction of the Th is transported in the river on particles, the rest is almost entirely carried by colloids.The Kalix River discharges into the Baltic Sea. Model calculations for the transport of Th and Ra isotopes in the Baltic Sea show that the high ratios of (234Th/238U)AR found here reflect long Th residence times relative to particle scavenging of ~50 d. The water column 232Th budget is dominated by eolian inputs. The 226Ra concentrations may be higher than those of water inflows, with =<60% derived from underlying sediments. A greater fraction of 228Ra is derived from sediments to balance the decay of 228Ra within the water column during the 35-yr residence time of water in the Baltic. The Baltic (228Ra/226Ra)AR ratios, which are relatively constant over a range of salinities, are fortuitously similar to those of the river inflows.